Luring, Daring, Hasil Belajar Perbedaan Pembelajaran Luring dan Daring Terhadap Hasil Belajar Siswa Pada Sub tema 1 “Sumber Energi” Kelas III Sekolah Dasar di Kota Soe - Matheos Salmon Nuban (Peneliti.net, 2021)
To prevent the transmission of Covid-19, the government applies distance learning (PJJ) using the offline and online learning method. This study uses the Nonequivalent Control Group Design, has two experimental groups that are not selected randomly. The aim of this study is to find out the difference between offline learning and online learning as seen from the learning outcomes of students. The sampling technique uses the type of Probability Sampling, namely Cluster Sampling (Area Sampling). The sample in this study was Grade 3, Elementary School students. The data collection instruments consisted of test questions and observations of teacher and student activities. The significant value is normal in the normality test and homogeneously distributed in the homogeneity test. Based on the results of the T-count on the T-test that has been carried out on the post-test scores of the experimental group 1 and experimental group 2, the T-count is 5.679 with Sig. (1-tailed) 0.000. Because it shows a significant value of less than 0.05, it means that Ho is rejected and Ha is accepted. Therefore, the conclusion is that the learning outcomes of sub-theme 1, 'Source of Energy' for Grade 3 using the offline learning model are significantly higher than the learning outcomes using the online model. This result is supported by the average post-test score in offline learning, which is 83.96 and the average post-test score in online learning is 73.33.